1995
DOI: 10.21273/hortsci.30.1.109
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fingerprints in Plants Using Simple-sequence Repeat and Minisatellite Probes

Abstract: Plant genomes contain polymorphic repetitive sequences that can be used as DNA markers. Minisatellites (16 to 64 bp per repeat) and simple-sequence repeats (2 to 6 bp per repeat) are the most polymorphic markers found in plant and animal genomes. In this study, the hybridizations between genomic DNA and variable number of tandem repeat probes were examined in Arabidopsis thaliana L. (Heynn), onion (Allium cepa L.), tomato … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…SSRs have therefore been widely utilized in plant genomic studies [33-36]. They are especially advantageous when there is a need to track desirable traits in large-scale breeding programs and when defining anchor points for map-based gene cloning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…SSRs have therefore been widely utilized in plant genomic studies [33-36]. They are especially advantageous when there is a need to track desirable traits in large-scale breeding programs and when defining anchor points for map-based gene cloning strategies.…”
Section: Discussionmentioning
confidence: 99%
“…DNA fingerprinting has earlier been called the hybridization of a genomic DNA blot with labelled microsatellite sequences, which makes corresponding target sequences visible throughout the genome (see Bruford et al, 1992, for an overview). The technique has been tried on A. cepa without success (Sharon et al, 1995;M. Klaas, unpublished results), even though the presence of corresponding sequences in A. cepa has been demonstrated by the successful generation of microsatellite markers (Fischer and Bachmann, 1998).…”
Section: Microsatellitesmentioning
confidence: 99%
“…Warude et al (2006) have reported on the development and application of RAPD-SCAR marker for the identification of Phyllanthus emblica (at the species level), however studies on the genetic variability of Aonla varieties employing molecular markers have not been attempted. It is very important to characterize the genetic variation using fool-proof methods such as DNA fingerprinting (Sharon et al, 1995) that can generate vital information on the varietal authentication especially in processing as this fruit has a prominent place in neutraceutical industry (Pathak, 2003). This study also finds immense application at the field level by way of The data presented here provide possibilities of identifying and differentiating most commonly cultivated varieties of P. emblica using 4 commercially available primers.…”
Section: Resultsmentioning
confidence: 99%